FEATURES OF USING FOREIGN LANGUAGE TERMINOLOGY IN THE PRACTICE OF PUBLICPRIVATE PARTNERSHIP IN RUSSIA - F. M. Ibyatov; M. A. Machulski; L. Yu. Vasilieva (Вестник университета)
Many terms in the Russian economy are of foreign origin. The use of foreign language concepts is a method of expanding economic terminology and research, facilitates international economic interaction. Many terms are assimilated and become generally applicable in the Russian economy. The article studies the issues related to the  use of foreign language terminology in the Russian practice of public-private partnership, considers the terms, categories and definitions of public-private partnership, both those which have been included in Russian science and practice, and those which have not been assimilated into the Russian language. The authors conclude that the use of foreign-language terms cannot be reduced simply to borrowing, it is necessary to adapt the borrowed words  and combinations to the Russian science and practice of public-private partnership; the use of borrowed  foreign language terms should not contradict the state concept of public-private partnership development and economic programs and strategies.